Suggested method of Estimation for the Two Parameters of Weibull Distribution Using Simulation Technique - ALNaqeeb, Abdulkhaleq; Hamad, Alaa (Iraqi Journal of Science, 2024)
In this paper, suggested method as well as the conventional methods (probabilityplot-(p.p.) for estimations of the two-parameters (shape and scale) of the Weibulldistribution had proposed and the estimators had been implemented for differentsample sizes small, medium, and large of size 20, 50, and 100 respectively bysimulation technique. The comparisons were carried out between different methodsand sample sizes. It was observed from the results that suggested method whichwere performed for the first time (as far as we know), by using MSE indicator, thecomparisons between the studied and suggested methods can be summarizedthrough extremely asymptotic for indicator (MSE) results by generating randomerrors with W(1, 1) and with generating with N(0,2  ) at the first contrast (1,1).The suggested method was reported better performance through the sequentiallystatus of ascending ordered for assumed initial contrast parameters, specially withgenerating of random error with W (1, 1) cooperation with generating of N (0,δ) inthe simple linear regression equation.